Assessments of Probiotic Potentials of Lactiplantibacillus plantarum Strains Isolated From Chinese Traditional Fermented Food: Phenotypic and Genomic Analysis - Sun, Yuwei; Zhang, Shiyao; Li, Hong; Zhu, Jiang; Liu, Zhijia; Hu, Xiaosong; Yi, Junjie (Frontiers in Microbiology, 2022)
The lack of rapid and effective approaches to determine the health benefits of strains is one of the main challenges affecting the selection of probiotics from large numbers of candidates. In this study, the probiotic potential of 44 Lactiplantibacillus plantarum strains isolated from different Chinese traditional fermented foods was evaluated, including acid and bile salt resistance, adhesion ability, survival in simulated human gastrointestinal transit, antioxidant activity, bile salt hydrolase (BSH) activity, and antibacterial activity. All tested L. plantarum strains showed high antioxidant capacity, BSH activity, and antibacterial activity. Among the strains, B652, C232, D444, and E932 were identified as the best comprehensive performed strains, which were selected for whole-genome sequencing, in order to provide clear information and identify key genes responsible for functional characteristics in vitro. It demonstrated that the antioxidant activity, adhesion activity, and ability to survive in the simulated gastric environment were found to be closely correlated with antioxidant enzyme encoding genes, cell-surface protein-encoding genes, and stress response genes, respectively. The numbers of functional genes present in strains might decide their performance in probiotic profile evaluation. The outcome of the study could support the development of a novel approach for the screening and identification of probiotics.